UPAYA INDONESIA MENANGGULANGI LIMBAH SAMPAH PLASTIK DARI BELANDA - Wanda "; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The problem of import plastic garbage describes that there is interest conflict between Netherland (exporter) and Indonesian (importer). Netherland doesn’t tend to process the produced plastic garbage and industry wastes, because the processing budget is enough expensive, moreover if the garbage includes dangerous and poisonous material. The easiest way to solve the garbage problem is exporting it into the third world countries including Indonesia.The method of data collecting is done by collecting secunder data, then analyzed in qualitative to obtain the draft about the main problem by using deductive method. The method of this research is the method of qualitative descriptive. The data is obtained through secunder data such as, book, journal, magazine, newspaper and website.From the result of research, that the coping with the plastic garbage import from Netherland that is implemented by Indonesian’s government by determining the Government Regulation Nr. 101 Year 2014 and doing the research project in developing innovative technology to collect the garbage in the river and the estuary through river clean up mechanism and paid plastic policy control. The use of plastic garbage is an effort to press the plastic removal and in certain limit increasing the dependency of import material.Keywords: Plastic garbage, Industry waste, Basel Convention